Desenvolvimento de produtos à base de plástico reciclado de embalagens de defensivos agrícolas: um estudo sobre cadeias de suprimentos regionais na ótica da Economia Circular - Pilla Jr., Paschoal José de (2023)
Circular Economy (CE) is associated with the practices of reducing, reusing, and recycling products and raw materials. This approach is particularly linked to product development processes, aiming for transitions from conventional and linear processes to more circular approaches. Plastic packaging used for agricultural pesticide storage, after use, is stored and later sent for recycling, covering long distances, incurring costs, and emitting polluting gases. This study aims to analyze the concept of Short Supply Chains (SSC) in the context of plastic packaging recycling, prioritizing the optimization of transportation, storage, and product development for local consumption. Based on in-depth interviews, this research adopts a case study approach to investigate supply chains that involve plastic packaging originating from the use of agricultural pesticides in the Alto Paranaíba and Triângulo Mineiro regions in Minas Gerais. The case study reveals that, although the current supply chain, which focuses on complying with legislation and providing proper disposal for used packaging, operates efficiently in terms of collection and recycling, the structure supporting this chain generates costs and inefficiencies leading to an operational deficit. The adoption of an SSC, in the context of pesticide packaging recycling and local production, refers to a more direct and proximate system between the stages of the supply chain, reducing physical distances and intermediaries, thus promoting a more efficient approach. Local recycling for the production of circular products, aiming to meet regional demand, can provide environmental, economic, and social benefits. However, these changes depend on redefining paradigms related to product development and current legislation, especially concerning packaging ownership. This research not only proposes a sustainable approach to plastic waste management but also highlights practical challenges that require concrete actions for the effective implementation of a shorter supply chain, aligning with sustainable development goals and generating significant economic and environmental benefits for the involved regions. While the study focuses on the agricultural sector, identifying specific opportunities, there is potential for its application in various segments, sectors, and regions. It is believed that the proposed approach is highly generalizable, potentially stimulating entrepreneurship in small and medium-sized local enterprises.